THE CATHETERIZATION AND ANGIOGRAPHIC VARIATIONS IN IRAQI PATIENTS WITH TETRALOGY OF FALLOT - Al-Hamash, Sadiq M. (Journal of the Faculty of Medicine Baghdad, 2005)
Background: Tetralogy of Fallot (TOF) is the most common form of cyanotic congenital heart disease and the catheterization and angiography still considered (in most centers) as essential preoperative diagnostic step. This retrospective aimed at evaluating the catheterization and angiographic finding in our Iraqi patients with diagnosis of TOF Patients and methods: The catheterization and angiographic study of200 patients with TOF-’ referred to Ibn Al-Bitar Cardiac Center had been reviewed. Results: There were 126 males and 74 females and their ages ranged from 11 months to 37 years. The catheterization data showed that 88% of the patients had equal LV and RV pressure. The evaluation of pulmonary artery pressure showed that all patients had normal pressure. The review of angiographic studies revealed that the perimembraneous VSDs were the most common type (91%> of the patients). 13 patients (6.5%) had coronary anomalies, and the patent ductus arteriosus is the most common associated anomalies. Conclusion: The frequency of doubly committed VSD and single coronary artery were higher than other studies and we showed there was no indication to measure the pulmonary artery pressure during catheterization.